Deorphanizing the human transmembrane genome: A landscape of uncharacterized membrane proteins - Babcock Joseph J; Li Min (Acta Pharmacologica Sinica, 2016)
Joseph J BABCOCK, Min LI* The Solomon H Snyder Department of Neuroscience, High Throughput Biology Center and Johns Hopkins Ion Channel Center (JHICC), School of Medicine, Johns Hopkins University, 733 North Broadway, Baltimore, MD 21205, USA The sequencing of the human genome has fueled the last decade of work to functionally characterize genome content. An important subset of genes encodes membrane proteins, which are the targets of many drugs. They reside in lipid bilayers, restricting their endogenous activity to a relatively specialized biochemical environment. Without a reference phenotype, the application of systematic screens to profile candidate membrane proteins is not immediately possible. Bioinformatics has begun to show its effectiveness in focusing the functional characterization of orphan proteins of a particular functional class, such as channels or receptors. Here we discuss integration of experimental and bioinformatics approaches for characterizing the orphan membrane proteome. By analyzing the human genome, a landscape reference for the human transmembrane genome is provided. Keywords: bioinformatics; human genome; membrane protein; orphan protein; ion channel; receptor; transporter; enzyme; drug targe We thank the Min LI laboratory for valuable discussions and Alison NEAL for editorial assistance. This work is supported by grants to Min LI from the National Institutes of Health (MH084691) * To whom correspondence should be addressed. E-mail minli@jhmi.edu Received 2013-07-28 Accepted 2013-09-08